Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 2702 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Mugil curema Valenciennes, 1836", "HasCoordinate is true", "HasGeospatialIssue is false" ] } The dataset includes 2702 records from 65 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0019719-151016162008034/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences